ASIMILASI ETNIK CINA DENGAN MELAYU (STUDI TERHADAP MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ISLAM RIAU) - Emilia Susanti (Lembaga penelitian dan pengabdian kepada Masyarakat, 2015)
Based on GRAND TOUR, Chinese ethnic students and Malay student s at economic faculty of Riau Islamic University are less communication. The Chinese uses Chinese to communicate at campus. Because of this problem the researcher wants to prove it by doing the research. The research purpose is to know about the students assimilation, supporting factors, unsupporting factors, and solution those are done by campus to solve the problem. The researcher uses qualitative method of Spran (1980). The data collection technique is used to get the information such as observation, interview, and documentation study. Informant of the research is determined by using Snow Ball sampling technique. The result of the research shows that Chinese students and Malay students communicate well, friendly, and harmonically. The factors those support the situation happens is because of the foundation leader, dean, and the official those raise conducive climate to the assimilation process. Meanwhile unconducive factors is caused by private assumption, economical social status, personal ability, and some students still do not use Indonesian to communicate at the campus. Some efforts and solution are done to solve the problem such as avoiding discriminative behavior, increasing moral message to some campus activities, and making conducive communicative condition at the campus.